Common Fixed Point Theorems for T-Hardy-Rodgers Contraction Mappings in Complete Cone b-Metric Spaces with an Application - Shashi Pauline; Kumar Santosh (Topological Algebra and its Applications, 2021)
This paper presents some fixed point theorems for T-Hardy-Rodgers contraction mappings in complete cone b-metric spaces without the assumption of normality conditions. We prove the existence of the common fixed point in complete cone b-metric spaces for the continuous self mappings. Our results generalize many recent known results in metric spaces, b-metric spaces and cone metric spaces in the literature.